Improving Health Consciousness and Life Skills in Young People Through Peer-Leadership in Thailand - Teerachote, C; Kessomboom, P; Rattanasiri, A; Koju, R (Kathmandu University Medical Journal, 2014)
Background Peer leadership is widely recognized as an effective approach to health promotion and empowerment among people of similar ages, especially the youth. Such programs build peer leaders who in turn help empower the youths in their groups to improve their health and life skills related to health. Most previous studies have focused on the effectiveness of such activities in target groups but have neglected to effectively address and explore the transformations in peer leaders themselves. Objectives This descriptive study aimed to investigate the level of social change and health consciousness among student peer leaders in three Youth health promotion programs in Thailand: Friend’s Corner, Smart Consumer and Volunteer Minded Young Dentists, and to compare them with the general students. Methods The study was conducted using a self-administered questionnaire, which was developed based on Tyree’s Social Change Model of leadership, Gould’s concept and Dutta-Bergman’s concept. The study population comprised of 11th grade students (N=660) from Kalasin Province in Thailand, 320 of whom were peer leaders. Results The findings revealed that the peer leaders scored higher than non peer leaders in all domains. Among the peer leaders, it was found that Volunteer Minded Young Dentists group had the highest scores in “controversy with civility”, “social change agent” characteristics, “holistic health perceptions” and “responsibility for one’s own health” regarding health consciousness. Conclusion The results of this study confirmed that the peer leadership approach can help young people to develop life skills through social transformation and increase health consciousness for better status of health in the community. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11025 Kathmandu University Medical Journal Vol.11(1) 2013: 41-44